2008
DOI: 10.1128/mcb.02065-07
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 Interacts with Acetylcholinesterase and Alters Its Enzymatic Activity and Glycosylation

Abstract: Presenilin 1 (PS1) plays a critical role in the ␥-secretase processing of the amyloid precursor protein to generate the ␤-amyloid peptide, which accumulates in plaques in the pathogenesis of Alzheimer's disease (AD). Mutations in PS1 cause early onset AD, and proteins that interact with PS1 are of major functional importance. We report here the coimmunoprecipitation of PS1 and acetylcholinesterase (AChE), an enzyme associated with amyloid plaques. Binding occurs through PS1 N-terminal fragment independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 81 publications
(113 reference statements)
4
34
0
Order By: Relevance
“…Accordingly, using non-denaturing polyacrylamide gels stained for AChE activity, molecular weights of AChE subunits are in the range of 70–75 kDa. However, analysis by SDS-PAGE and Western blotting by us and others, under fully reducing conditions and with several different anti-AChE antibodies, detected bands ranging from 75 to 50 kDa, for the AChE protein from different sources and animal species, including humans [30], [37], [44], [56][60]. The specificity of the 78 kDa AChE bands and of the lower molecular weight AChE bands was confirmed by immunoprecipitation, Fas2 affinity matrix binding and immunodetection of blots with different anti-human AChE antibodies (including the N-terminal N-19 and the ab31276 antibody, which recognizes the C-terminal residues 601–614 of human AChE-T) and is in agreement with our previous study in human CSF [30].…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, using non-denaturing polyacrylamide gels stained for AChE activity, molecular weights of AChE subunits are in the range of 70–75 kDa. However, analysis by SDS-PAGE and Western blotting by us and others, under fully reducing conditions and with several different anti-AChE antibodies, detected bands ranging from 75 to 50 kDa, for the AChE protein from different sources and animal species, including humans [30], [37], [44], [56][60]. The specificity of the 78 kDa AChE bands and of the lower molecular weight AChE bands was confirmed by immunoprecipitation, Fas2 affinity matrix binding and immunodetection of blots with different anti-human AChE antibodies (including the N-terminal N-19 and the ab31276 antibody, which recognizes the C-terminal residues 601–614 of human AChE-T) and is in agreement with our previous study in human CSF [30].…”
Section: Discussionmentioning
confidence: 85%
“…We have recently demonstrated an interaction between AChE and presenilin-1 (PS1), the catalytic component of the γ-secretase complex (Silveyra et al, 2008;2012a). γ-Secretase is a proteolytic enzymatic complex that participates in the processing of the amyloid precursor protein (APP), generating the β-amyloid peptide or Aβ (Kaether et al, 2006), the major constituent of the amyloid plaques (Masters et al, 1985;Kang et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been suggested that both Ab and tau induce the altered glycosylation of the cholinesterases [78]. It has been reported that PS1 interacts with AChE, and affects the enzymatic activity and glycosylation of the enzyme [86]. Reelin is another protein involved in regulating synaptic function and plasticity that has altered glycosylation properties in AD.…”
Section: Other Proteins Of Relevance To Admentioning
confidence: 99%